Infants’ expectations about gestures and actions in third-party interactions - Thorgrimsson, Gudmundur B.; Fawcett, Christine; Liszkowski, Ulf (Frontiers in Psychology, 2014)
We investigated 14-month-old infants’ expectations toward a third party addressee of communicative gestures and an instrumental action. Infants’ eye-movements were tracked as they observed a person (the Gesturer) point, direct a palm-up request gesture, or reach toward an object, and another person (the Addressee) respond by grasping it. Infants’ looking patterns indicate that when the Gesturer pointed or used the palm-up request, infants anticipated that the Addressee would give the object to the Gesturer, suggesting that they ascribed a motive of request to the gestures. In contrast, when the Gesturer reached for the object, and in a control condition where no action took place, the infants did not anticipate the Addressee’s response. The results demonstrate that infants’ recognition of communicative gestures extends to others’ interactions, and that infants can anticipate how third-party addressees will respond to others’ gestures.